ANALISIS PENGARUH PEMBERDAYAAN ZAKAT PRODUKTIF TERHADAP PENGENTASAN KEMISKINAN MUSTAHIK DENGAN KETERAMPILAN SEBAGAI VARIABLE MODERASI - Erni Susilawati (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the effect of productive zakat empowerment on poverty alleviation among mustahik and to examine the moderating role of skills among beneficiaries of productive zakat programs administered by BAZNAS Pandeglang Regency. A quantitative approach was employed using a survey method involving productive zakat beneficiaries. Data were analyzed using linear regression and Moderated Regression Analysis (MRA). The findings indicate that productive zakat empowerment positively contributes to poverty alleviation by improving economic capacity and business independence among mustahik. Furthermore, skills strengthen the relationship between productive zakat empowerment and poverty reduction. Beneficiaries with higher skill levels are able to utilize productive assistance more effectively, resulting in more sustainable welfare improvements. These findings highlight the importance of integrating financial support, training, and skill development within zakat-based empowerment programs to enhance their effectiveness in alleviating poverty.